Gap analysis and methodological framework to assess and develop water centric sustainable agricultural intensification pathways in Sub-Saharan Africa - Haileslassie, Amare; Mekuria, Wolde; Uhlenbrook, Stefan; Ludi, Eva; Schmitter, Petra (Frontiers in Water, 2022)
The sustainable agricultural intensification (SAI) debate was partly rooted in discussions over the Green Revolution and further coined in the 1990s in the context of smallholder agriculture in Africa. However, production is still largely rainfed, significant yield gaps prevail, and the environment is rapidly degrading in many countries. Projections indicate that climate and demographic changes will intensify competition for freshwater resources. Currently, SAI has mainly centered around, predominantly, rain-fed agricultural systems and often at a farm scale. With the increasing attention to the improved role of agricultural water management (AWM) to address these challenges, in SSA, the question arises as to how the SAI framework facilitates better understanding and planning of the agricultural landscape along the rain-fed -irrigation continuum. Accordingly, this paper reviews the gaps in concepts and practices of SAI and suggests a methodological framework to design context-specific and water-centered sustainable intensification pathways (SIP). Given the gaps of SAI practices, the proposed methodological framework demonstrates: a) how to couple sustainability assessment methods to participatory SIPs design and adaptive management approach; b) how contextualized sustainability domains and indicators can help in AWM centered SIP development; c) approaches to handle water-related indicators, the heterogeneity of biophysical and social settings when tailoring technology options to local contexts; and d) principles on which sustainable intensification pathways design depends to enable synergies and complementarities of SAI measures to reinforce the rainfed-irrigation continuum. The proposed methodological framework helps researchers to integrate sustainability assessment and design of SIP, and guides policymakers and practitioners on how to plan, implement, and monitor SAI across multiple scales.